Factors associated with confidence in decision making and satisfaction with risk communication among patients with atrial fibrillation. (June 2018) - Hedberg, Berith; Malm, Dan; Karlsson, Jan-Erik; Årestedt, Kristofer; Broström, Anders
Background: Atrial fibrillation is a prevalent cardiac arrhythmia. Effective communication of risks (e.g. stroke risk) and benefits of treatment (e.g. oral anticoagulants) is crucial for the process of shared decision making. Aim: The aim of this study was to explore factors associated with confidence in decision making and satisfaction with risk communication after a follow-up visit among patients who three months earlier had visited an emergency room for atrial fibrillation related symptoms. Methods: A cross-sectional design was used and 322 patients (34% women), mean age 66.1 years (SD 10.5 years) with atrial fibrillation were included in the south of Sweden. Clinical examinations were done post an atrial fibrillation episode. Self-rating scales for communication (Combined Outcome Measure for Risk Communication and Treatment Decision Making Effectiveness), uncertainty in illness (Mishel Uncertainty in Illness Scale–Community), mastery of daily life (Mastery Scale), depressive symptoms (Hospital Anxiety and Depression Scale) and vitality, physical health and mental health (36-item Short Form Health Survey) were used to collect data. Results: Decreased vitality and mastery of daily life, as well as increased uncertainty in illness, were independently associated with lower confidence in decision making. Absence of hypertension and increased uncertainty in illness were independently associated with lower satisfaction with risk communication. Clinical atrial fibrillation variables or depressive symptoms were not associated with satisfaction with confidence in decision making or satisfaction with risk communication. The final models explained 29.1% and 29.5% of the variance in confidence in decision making and satisfaction with risk communication. Conclusion: Confidence in decision making is associated with decreased vitality and mastery of daily life, as well as increased uncertainty in illness, while absence of hypertension and increased uncertainty in illness are associated with risk communication satisfaction.